Performance Measurement of a Private Hospital during the Pandemic Covid-19 - Yuyun Umniyatun; Kris Febyta Aulia; Sri Rahayu; Teuku Nebrisa Zagladin Jacoeb; Mochammad Iqbal Nurmansyah (Universitas Prasetiya Mulya, 2023)
This study aims to analyze the performance of private hospitals during the COVID-19 pandemic through the BSC approach. This research uses a quantitative descriptive approach based on a case study at a private hospital in East Jakarta. A hospital employee-patient survey provided the main data. 2019–2020 hospital reports supplied secondary data. The results showed that, from the customer perspective, there was a decrease in performance in customer acquisition and retention. From the internal business process perspective, there is a decrease in bed occupancy rate and turnover interval. From a financial perspective, there is a decline in profitability and cost recovery rate. The learning perspective is considered good in employee satisfaction, low employee turnover, and regular training, so that it can be concluded that employee retention is well implemented. Overall, hospitals need to review key performance indicators from a customer perspective and internal business processes to improve financial performance.